Case Report: An exploration of the neurodevelopmental phenotype of five patients with 48,XXYY during early childhood years - Olaya, Margaret; Samango-Sprouse, Carole; Counts, Debra; Kline, Antonie D.; Mitchell, Francie; Buscema, Elizabeth; Tipton, Elizabeth; Sadeghin, Teresa; Gropman, Andrea L. (Frontiers in Endocrinology, 2025)
Background48,XXYY is a sex chromosome aneuploidy (SCA) occurring in 1:18,000–50,000 male births, characterized by androgen deficiency in conjunction with hypogonadism, hypertelorism, clinodactyly, pes planus, radioulnar synostosis, increased height velocity, hypotonia, and a suspected increased incidence of autism spectrum disorder (ASD). The neurodevelopmental phenotype includes motor dysfunction, speech/language disturbance, and intellectual deficits.AimThis series will compare the neurodevelopmental profile of five patients with 48,XXYY during early childhood.MethodsFive cases of male patients with 48,XXYY were followed beginning at the time of diagnosis. Each case underwent a combination of neurodevelopmental, oral motor, speech/language, physical therapy, medical genetics, and/or neurology evaluations.ResultsIn the five cases presented, there was an increased incidence of torticollis, with the right side more common. Abnormal muscle tonus was noted in all cases, characterized by hypotonia of the trunk, upper extremities, and oral motor musculature. Four of the patients exhibited an increased head circumference (≥ 79th percentile) by 7 months of age. All cases had speech/language and motor delays evident in the first 12 months of life and showed no signs of ASD prior to 3 years of age.ConclusionsThe presentation of 48,XXYY is varied, including oral motor deficits, hypotonia, positional and congenital muscular torticollis, respiratory issues, and inner-ear dysfunction. Early presentations of infantile developmental dyspraxia are evident by 18 months, specifically as discrepancies between fine and gross motor and expressive and receptive language skills. This series provides additional insight into the phenotypic presentation of male patients with 48,XXYY during infancy and early childhood and identifies common complications.